New Series of Red-Light Phosphor Ca9−xZnxGd0.9(PO4)7:0.1Eu3+ (x = 0–1) - Yury Yu. Dikhtyar; Dmitry A. Spassky; Vladimir A. Morozov; Sergey N. Polyakov; Valerya D. Romanova; Sergey Yu. Stefanovich; Dina V. Deyneko; Oksana V. Baryshnikova; Ivan V. Nikiforov; Bogan I. Lazoryak (Molecules, 2023)
In this study, a new series of phosphors, Ca9−xZnxGd0.9(PO4)7:0.1Eu3+ (x = 0.00–1.00, step dx 0.05), was synthesized, consisting of centro- and non-centrosymmetric phases with β-Ca3(PO4)2-type structure. Crystal structures with space groups R3c (0.00 ≤ x < 0.35) and R<semantics><mover accent="true">3¯</mover></semantics>c (x > 0.8) were determined using X-ray powder diffraction and the method of optical second harmonic generation. In the region 0.35 ≤ x ≤ 0.75, phases R3c and R<semantics><mover accent="true">3¯</mover></semantics>c were present simultaneously. Refinement of the Ca8ZnGd(PO4)7 crystal structure with the Rietveld method showed that 71% of Gd3+ ions are in M3 sites and 29% are in M1 sites. A luminescent spectroscopy study of Ca9−xZnxGd0.9(PO4)7:0.1Eu3+ indicated the energy transfer from the crystalline host to the Gd3+ and Eu3+ luminescent centers. The maximum Eu3+ luminescence intensity corresponds to the composition with x = 1.